Synergy of Knowledge Management and Dynamic Capabilities Driving Innovation in East Java's SMEs Growth - Khurotul Aini, Edlyn; Sandy Yuliaji, Eliana (Profit: Jurnal Adminsitrasi Bisnis, 2026)
This study investigates how Knowledge Management Capability (KMC), Dynamic Capability (DC), and Innovation Ambidexterity (IA) relate to Business Performance (BP) among MSMEs in East Java. A quantitative survey design was applied by distributing questionnaires to MSMEs in the province. Using non-probability sampling and Cochran’s formula, the study recruited 96 MSMEs as respondents. The results show that KMC has a significant positive effect on DC and also shapes IA. In addition, DC plays a significant role in strengthening IA, suggesting that adaptive organizational capabilities are crucial for developing balanced innovation. However, IA does not directly improve BP, which differs from common theoretical assumptions. Moreover, Environmental Turbulence (ET) does not moderate the relationship between IA and BP, suggesting that uncertain external conditions do not change whether IA translates into performance outcomes. Overall, the study clarifies the mechanisms through which KMC and DC support IA, while also revealing limits in how IA contributes to performance. These insights offer a more targeted perspective on capability-building for MSMEs in East Java, adding nuance to discussions on innovation and performance in developing economies.